Gut transit rate in Atlantic salmon (Salmo salar) exposed to optimal and suboptimally high water temperatures. (29th June 2022) - Mock, Thomas S.; Alkhabbaz, Zakarya H. R. A. A.; Rocker, Melissa M.; Lewis, Michael J.; Cumming, Erin E.; Smullen, Richard P.; Turchini, Giovanni M.; Francis, David S.
Abstract: The gut transit rate of ingested feed in fish affects the utilization of dietary nutrients; however, the influence of water temperature, remains underexplored in Atlantic salmon ( Salmo salar ). The present study quantified the gut transit rate of four distinct regions of the gastrointestinal tract (stomach, pyloric caeca, small and large intestine) of post‐smolt Atlantic salmon at two temperatures; 11 and 20°C, by feeding fish a diet incorporated with Ballotini beads. A determination of relative and total bead density in each region was assessed for 48 h, post‐feeding. A clear inverse relationship in bead density between the stomach and large intestine was recorded at both temperatures. However, fish subjected to 20°C recorded a faster gut transit rate compared to fish at 11°C in both the stomach and large intestine. The pyloric caeca and small intestine transit rate appeared unaffected by temperature. The present study re‐iterates the positive relationship between temperature and gut transit rate and also the critical function of the stomach in controlling gut transit rate in gastric fish. This information may be used to improve dietary strategies aimed at enhancing nutrient utilization through increased understanding of the gut transit rate in commercially important fish species.